ANALYSIS OF THE INFLUENCE OF FINANCIAL INSTITUTIONS AND BANKING STABILITY ON THE HUMAN DEVELOPMENT INDEX IN BRICS - Monika Sapitri; Siti Rohima; Mu’izzuddin Mu’izzuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the relationship between financial institutions and banking stability and the Human Development Index. The BRICS countries, specifically Brazil, Russia, China, India, Indonesia, and South Africa, were sampled. Secondary data from the UNDP, IMF, and World Bank were used. The analysis technique used in this study was panel data regression for the period 2000–2022. The results of the fixed effect model estimation indicate that financial institutions and banking stability have a positive and complementary effect on improving the Human Development Index (HDI) in BRICS countries. Inclusive financial institutions promote access to basic services. Banking stability strengthens economic confidence and supports the financing of social development.